Pakistan: working cross-culturally using an ACEs and trauma framework. Is it possible? - Lisa Cherry (Scottish Journal of Residential Child Care)
This article sets out to explore cross cultural potential for using the framework of ACE's and Trauma Informed Practice through the learning encountered by the author on two trips to Lahore in 2017 and 2018. The author explores the complex layers that facilitate some of the challenges to this but also how they may lead the way in providing some of the answers. The author concludes that it is possible but only in the context of curiosity, shared conversations and humility about the diversity of human experience.